Evaluation of Ecosystem-Based Small Pelagic Fisheries Management in Fish Resources Domains in North Sulawesi Waters as a Blue Economy Implementation - Lasabuda, Ridwan; Wagey, Billy Theodrus; Kondoy, Khristin I.F (Sam Ratulangi University, 2026)
This study evaluates the management of small pelagic fisheries, specifically focusing on the mackerel scad (Decapterus macarellus), in North Sulawesi waters through the Ecosystem Approach to Fisheries Management (EAFM) framework within the Fish Resources Domain. Conducted at PPP Tumumpa, Manado, between March and November 2025, the research utilized surveys, interviews, and literature reviews. Performance was assessed using Multi-Criteria Analysis (MCA) across six key indicators: standardized CPUE, fish size trends, juvenile proportion, species composition, range collapse, and ETP (Endangered, Threatened, and Protected) species. The results indicate that management performance is highly effective, with a composite value of 85, placing it in the